Rapid diagnosis of respiratory syncytial virus infection in children by the immunofluorescent technique - Cradock-Watson, J. E. (1971)
The immunofluorescent examination of nasopharyngeal secretions has been compared with conventional cell culture for the diagnosis of respiratory syncytial (RS) virus infection in children under the age of 2 years in Newcastle upon Tyne and Manchester. Two hundred and sixty-eight identifications of RS virus were made by the fluorescent method, of which 258 (96%) were confirmed culturally. In 267 children from whom virus was isolated in cell culture a positive diagnosis was made by the fluorescent method in 258 (97%). In 238 infants with bronchiolitis a diagnosis of RS virus infection was made on the basis of the fluorescent test in 185 (78%) of which 180 (97%) were subsequently confirmed in cell culture. The reasons for false results are briefly discussed. It is concluded that the method is reliable for the early diagnosis of respiratory syncytial virus infection.